Performance evaluation of five species of oyster mushroom Pleurotus spp.) on various agro-wastes in North-western Himalayas - Kumar, Ravinder; Hooda, K S; Bhatt, J C; Kumar, R Arun; Singh, G (Mushroom Research, 2012)
Cultivation of Pleurotus species (P. sajor-caju, P. florida, P. flabellatus, P. fossulatus and P. sapidus) on different substrates were tried such as wheat straw (WS), Brassica straw (BS), lentil straw (LS) alone and WS in combination with BS and LS in 1:1, 2:1 and 1:2 ratios. The substrates straw were chemically treated (carbendazim 7.5 g and formalin 100ml/100 litre) over night (Vijay and Sohi, 1987) and recommended package of practice was followed. After the first two flushes, the spawn run blocks were over turned to allow the lower surface and the base to produce fruiting bodies. WS+LS (1:1 and 2:1) was found to be the most suitable substrate combination for the faster spawn run and pin head initiation at least by 3-4 days than other substrates/ combinations. Â